Kerentanan Sosio-Ekonomi terhadap Paparan Bencana Banjir dan Rob di Pedesaan Pesisir Kabupaten Demak - Iwan Rudiarto; Dony Pamungkas; Hajar Annisa; Khalid Adam (Jurnal Wilayah dan Lingkungan, 2016)
Disaster is an event which suddenly or slowly occurs caused by human, nature, or even both. Disaster is not only related to the physical environment where disaster found but also to the livelihood of the community. Coastal rural is vulnerable to the coastal disaster such as flood and tidal flood due to their high dependency on the coastal resources. The vulnerability assessment of the coastal rural is very important in order to identify the level of vulnerability and to recommend crucial strategies for reducing the risk of disaster exposure in the future. This study aims to identify the socio-economic vulnerability in the rural coastal community of Demak Regency. Vulnerability assessment was carried out through a spatial explicit modeling. The results showed that 33 villages equivalent to 42% out of the total 78 villages were categorized as most vulnerablesocially and economically. The remaining 45 villages accounted for 58% were less vulnerable. Therefore, efforts on the disaster mitigation are necessary to reducing the exposure impact to the coastal rural community.